The Cause of Unexpected Acute Abdomen and Intra-Abdominal Hemorrhage in 24-Week Pregnant Woman: Bochdalek Hernia - Yavuz Savas Koca; Ibrahim Barut; İhsan Yildiz; Rasih Yazkan (Case Reports in Surgery, 2016)
Bochdalek hernia (BH) is the most common type of congenital diaphragm hernia and is rarely seen in adults. In adult patients, BH often remains asymptomatic or presents with nondiagnostic symptoms and may lead to complications, though rarely. The necrosis and perforations occurring in the hernia may lead to mortality. In this report, we present a 34-year-old pregnant woman at 24 gestational weeks who presented with Bochdalek hernia causing gastric volvulus associated with perforation and intra-abdominal hemorrhage associated with splenic rupture.